Metagenomic analysis of contaminated lift buttons reveals prevalent pathogens with antimicrobial resistance genes: a study in a public hospital in Pahang, Malaysia - Muhammad, Izzati; Samsuddin, Niza; Raja Abdul Rahman, Raja Noor Zaliha; Kamarudin, Norhidayah; Alias, Norsyuhada (IIUM Press, 2024)
Introduction: Hospital lift buttons are potential reservoirs for microbial contamination, contributing to the transmission of hospital-acquired infections (HAIs). Despite routine cleaning efforts, concerns persisted regarding the prevalence of contaminants on these surfaces, particularly in healthcare settings within Southeast Asian countries. This study aimed to investigate the prevalence and microbial diversity of contaminants on lift buttons in a public hospital (PH) located in Pahang, Malaysia, during the coronavirus disease 2019 pandemic. Methods: Purposive swab sampling was conducted thrice at two-week intervals. Standard plate count and metagenomic analysis were employed to determine the prevalence of contaminants and identify the diverse microbial communities, respectively. Analysis of variance and Bonferroni test evaluated at alpha value less or equal to 0.05, were performed to determine the significance of the findings. Results: The investigation revealed a notable prevalence of contaminants at 30.4% on both interior and exterior lift buttons, with no significant disparity observed between lifts in high-risk and moderate-risk areas (p>0.05). Metagenomic analysis revealed Firmicutes as the dominant phylum, with Staphylococcus and Bacillus being the most prevalent genera. Analysis of the Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathways highlighted the importance of ABC transporter and two-component systems, where key genes involved in the iron complex transport, antimicrobial resistance, and multidrug efflux enriched, crucial for the microbial survival. Conclusion: These findings underscored the complexity of microbial ecosystems and their adaptive mechanisms in response to environmental pressures, while emphasizing the importance of implementing effective infection control measures to mitigate the risk of lift buttons-associated HAIs. Future research should broaden the geographical scope to encompass diverse hospital settings and explore the interaction of microbial communities’ functional capabilities with the hospital environment, offering insights into optimizing hygiene practices and targeted intervention.